Biodegradable plastic as well as preparation method and application thereof

DNA-based biodegradable plastics prepared through two-way frozen casting, freeze-drying, water vapor annealing and compression densification steps, solve the problems of high energy consumption, environmental pollution and raw material competition in the production and use of existing biodegradable plastics. At the same time, the strength of DNA-based biodegradable plastics is improved, achieving high toughness and environmentally friendly and degradable effects, and is suitable for multiple application fields.

CN119610802AActive Publication Date: 2025-03-14SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411633183.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-14
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing biodegradable plastics based on cellulose, starch and protein have problems such as high energy consumption, environmental pollution and raw material competition during production and use. At the same time, the strength of DNA-based biodegradable plastics is insufficient, making it difficult to meet the practical application requirements.

Method used

DNA-based biodegradable plastics with a natural nacre structure similar to that of onion DNA were prepared by steps such as water dissolution, bidirectional freeze casting, freeze-drying, water vapor annealing and compression densification.

Benefits of technology

The prepared biodegradable plastics have both high toughness and environmentally friendly and degradable properties. They are suitable for packaging, medical devices, 3D printing, agricultural tools and environmentally friendly consumer products and are suitable for large-scale industrial production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610802A_ABST
    Figure CN119610802A_ABST
Patent Text Reader

Abstract

The invention discloses biodegradable plastic as well as a preparation method and application thereof. The preparation method of the biodegradable plastic comprises the following steps: 1) dissolving onion DNA in water to prepare a DNA solution; 2) injecting the DNA solution into a mold for bidirectional freezing casting to obtain a DNA frozen block; (3) carrying out freeze drying on the DNA frozen block to obtain a DNA aerogel block; 4) annealing the DNA aerogel block in a water vapor environment to obtain an annealed DNA aerogel block; and (5) stacking a plurality of annealed DNA aerogel blocks, and carrying out compression densification, so as to obtain the biodegradable plastic. The biodegradable plastic has the characteristics of high toughness and environmental friendliness and degradability, is wide in raw material source and simple in preparation method, can be applied to the fields of packaging, medical instruments, 3D printing, agricultural tools, environment-friendly consumer products and the like, and is suitable for large-scale industrial production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmentally friendly materials, and in particular to a biodegradable plastic and a preparation method and application thereof. Background Art

[0002] Plastics (petroleum-based) are ubiquitous in our daily lives and play an important role, but they are difficult to recycle and the environmental pollution they cause cannot be ignored. Biodegradable plastics are a type of plastic that can be degraded by microorganisms (such as bacteria, molds, and algae) that exist in nature. Compared with traditional plastics, they are more environmentally friendly and have broader application prospects.

[0003] At present, raw materials such as cellulose, starch and protein have been used in biodegradable plastics, but biodegradable plastics based on these raw materials generally have the following problems in production and use: 1) Processing requires high temperature and hot pressure, which consumes a lot of energy; 2) Modification requires the use of a large amount of organic solvents, which causes environmental pollution and produces by-products; 3) Raw materials come from crops, which will form a competitive relationship with agricultural resources such as farmland and water. Deoxyribonucleic acid (DNA), as a natural polymer, has good biocompatibility and degradability, and is suitable for the preparation of biodegradable plastics. However, the strength of biodegradable plastics based on DNA is far inferior to that of other bio-based degradable plastics and petroleum-based plastics, and it is difficult to fully meet the requirements of practical applications, and its application is greatly limited.

[0004] Therefore, it is of great significance to develop a highly tough biodegradable plastic based on DNA. Summary of the invention

[0005] The purpose of the present invention is to provide a biodegradable plastic and a preparation method and application thereof.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing biodegradable plastics comprises the following steps:

[0008] 1) Dissolve onion DNA in water to prepare a DNA solution;

[0009] 2) injecting the DNA solution into the mold for two-way freezing casting to obtain a DNA freezing block;

[0010] 3) freeze-drying the DNA frozen block to obtain a DNA aerogel block;

[0011] 4) placing the DNA aerogel block in a water vapor environment for annealing to obtain an annealed DNA aerogel block;

[0012] 5) stacking a plurality of annealed DNA aerogel blocks and then compressing and densifying them to obtain biodegradable plastic.

[0013] Preferably, the onion DNA in step 1) is prepared by a preparation method comprising the following steps: rapidly freezing onions and then crushing them to prepare onion powder, adding the onion powder to a mixed solution of CTAB extraction buffer and 2-mercaptoethanol for incubation, adding chloroform and isoamyl alcohol and centrifuging, taking the clear liquid for alcohol precipitation, centrifuging, and taking the solid matter for washing and drying to obtain the onion DNA.

[0014] Preferably, the rapid freezing comprises the following steps: adding the onions into liquid nitrogen for freezing.

[0015] Preferably, the volume ratio of the CTAB extraction buffer to 2-mercaptoethanol is 20-30:1.

[0016] Preferably, the incubation is carried out at a temperature of 60° C. to 70° C., and the incubation time is 40 min to 60 min.

[0017] Preferably, the volume ratio of chloroform to isoamyl alcohol is 20-30:1.

[0018] Preferably, the washing comprises the following steps: first washing with anhydrous ethanol, then washing with an ethanol solution with a mass fraction of 70% to 80%, and finally washing with water for multiple times.

[0019] Preferably, the mold in step 2) is in the shape of a cube or a rectangle, and a polydimethylsiloxane (PDMS) right triangular prism is arranged inside. The bottom surface of the PDMS right triangular prism is a right triangle, and the two right-angled sides of the right triangle are respectively attached to the bottom and side wall of the mold.

[0020] Preferably, the bidirectional freeze casting in step 2) is carried out at a temperature of -80°C to -60°C, and the casting time is 30 min to 60 min.

[0021] Preferably, the freeze-drying in step 3) is carried out under the conditions of a pressure of 3Pa to 7Pa and a temperature of -70°C to -50°C, and the freeze-drying time is 48h to 72h.

[0022] Preferably, the annealing in step 4) is carried out in a water vapor environment with a relative humidity of 60% to 80%, and the annealing time is 15 min to 25 min.

[0023] Preferably, the compression densification in step 5) is carried out at a pressure of 10 MPa to 15 MPa, and the pressure holding time is 30 min to 40 min.

[0024] A biodegradable plastic is made by the above preparation method.

[0025] An application of the biodegradable plastic as described above in the fields of packaging, medical devices, 3D printing, agricultural tools or environmentally friendly consumer products.

[0026] The beneficial effects of the present invention are as follows: the biodegradable plastic of the present invention has the characteristics of high toughness and environmentally friendly degradability, and its raw material sources are wide and the preparation method is simple. It can be used in packaging, medical equipment, 3D printing, agricultural tools and environmentally friendly consumer products and other fields, and is suitable for large-scale industrial production and application.

[0027] Specifically:

[0028] The present invention prepares a DNA-based biodegradable plastic having a structure similar to that of natural nacre (shell biomaterials have a multi-scale structure, including orderly arranged mineral crystals at the microscopic level and a protein matrix at the macroscopic level. When subjected to external impact, the mineral crystals at the microscopic level can effectively disperse and absorb stress, while the protein matrix helps to prevent crack propagation. The coordination of the interaction of this multi-scale structure enables shell materials to exhibit excellent toughness and impact resistance) through bidirectional freezing, steam annealing and compression densification. The plastic has a multi-scale hierarchical structure, exhibits excellent toughness and impact resistance, is recyclable and biodegradable, can be used in many fields such as packaging, medical devices, 3D printing, agricultural tools and environmentally friendly consumer products, and is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a flow chart for preparing the biodegradable plastic.

[0030] Figure 2 This is a graph showing the color change of the onion DNA solution in the example measured by the diphenylamine method.

[0031] Figure 3 It is the ultraviolet absorption spectrum of the onion DNA solution in the embodiment.

[0032] Figure 4 The following are SEM images and physical images of the biodegradable plastics in the embodiments and comparative examples.

[0033] Figure 5 The stress-strain curves obtained by uniaxial tensile testing of the biodegradable plastics in the embodiments and comparative examples and the corresponding Young's modulus and tensile work test result diagrams are shown.

[0034] Figure 6 The force-displacement relationship curves obtained by performing three-point bending fracture tests on the biodegradable plastics in the embodiments and comparative examples.

[0035] Figure 7Comparative curves of elastic contribution, plastic contribution and toughness of the biodegradable plastics in Examples and Comparative Examples.

[0036] Figure 8 Schematic diagram of the recycling of biodegradable plastics in the embodiment.

[0037] Fig. 9 The optical photographs are of the morphological changes of the biodegradable plastics in the examples at different time points during the degradation process and the gel electrophoresis band diagram after complete biodegradation. DETAILED DESCRIPTION

[0038] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0039] Example:

[0040] A biodegradable plastic, the preparation method thereof is as follows (the preparation flow chart is as follows Figure 1 shown):

[0041] 1) Add 0.3 g of onion DNA to 10 mL of deionized water and shake at room temperature for 20 min to obtain a DNA solution (uniform and transparent);

[0042] 2) The DNA solution is injected into the mold. The mold is in the shape of a cube, and a PDMS right triangular prism is arranged inside. The bottom surface of the PDMS right triangular prism is a right triangle. The two right-angled sides of the right triangle are respectively attached to the bottom and side wall of the mold. The bottom end of the mold is in contact with a cold trap (liquid nitrogen is used to make the cold source, and a copper bridge is used to conduct the cold source). Bidirectional freezing casting is performed at -70°C for 40 minutes to obtain a DNA frozen block;

[0043] 3) The DNA frozen block was taken out from the mold, and then placed in a freeze dryer for freeze drying at a pressure of 5 Pa and a temperature of -60°C for 48 hours to obtain a DNA aerogel block;

[0044] 4) placing the DNA aerogel block in a water vapor environment with a relative humidity of 70% and annealing for 20 minutes to obtain an annealed DNA aerogel block;

[0045] 5) stacking two annealed DNA aerogel blocks in a hot press and vertically compressing them for 35 minutes at room temperature and a pressure of 10 MPa to obtain biodegradable plastic.

[0046] Note:

[0047] The preparation method of onion DNA is as follows:

[0048] a) immersing the onion in liquid nitrogen (-196°C) for rapid freezing, then taking it out and grinding it into fine powder in a sterile mortar to obtain onion powder;

[0049] b) Preheat 250 mL of CTAB extraction buffer to 65°C, add 10 mL of 2-mercaptoethanol and mix thoroughly, add onion powder and stir, then incubate in a 65°C water bath for 45 min, add 240 mL of chloroform and 10 mL of isoamyl alcohol, stir, add to a centrifuge, centrifuge at 12000 rpm for 10 min, collect the clear liquid, repeat the centrifugation twice, take the clear liquid and add 500 mL of 0°C anhydrous ethanol for alcohol precipitation (white flocculent precipitate), add to a centrifuge, centrifuge at 5000 rpm for 5 min, wash the solid with anhydrous ethanol, then with 75% by mass ethanol solution, then wash 3 times with deionized water, and freeze-dry at -60°C for 60 h to obtain onion DNA.

[0050] Comparative Example:

[0051] A biodegradable plastic, which is exactly the same as the embodiment except that step 2) is adjusted to "injecting the DNA solution into the mold (without PDMS straight triangular prisms inside), and freeze-molding at -70°C for 40 minutes (the cooling temperature of the mold is random and uniform)".

[0052] Performance Testing:

[0053] 1) Add 1 mL of diphenylamine reagent (acidic) to 1 mL of the onion DNA solution in the example, and then observe the color change of the DNA solution under heating conditions. The test results are as follows: Figure 2 (deionized water was used as reference).

[0054] Depend on Figure 2 It can be seen that after the DNA solution in the embodiment is fully mixed with the diphenylamine reagent, it is observed that the mixed solution gradually turns blue. The mechanism of color change is: under acidic heating conditions, the glycosidic bond between the base and deoxyribose on the DNA molecular chain is broken, and the ω-hydroxy-γ-ketopentanal generated by dehydration condensation of deoxyribose under this condition reacts with diphenylamine to undergo a Schiff base reaction to ultimately generate a blue substance 2,5-bis(diphenylamino)pentan-1-ol; as a control, an equal volume of deionized water was used instead of the DNA solution, and the experiment was carried out according to the same steps, and it was observed that the mixed solution did not change color, indicating that no DNA was present in the mixed solution.

[0055] 2) The ultraviolet absorption spectrum of the DNA solution in the embodiment is as follows Figure 3 shown.

[0056] Depend on Figure 3It can be seen that: based on the A260 reading on the ultraviolet absorption spectrum curve and the conversion factor (1 A260 unit = 50 μg / mL DNA solution), the concentration of the DNA solution in the embodiment is calculated to be 28 ng / μL; the characteristic peaks at 260nm and 230nm in the ultraviolet absorption spectrum are the markers for determining DNA.

[0057] 3) The scanning electron microscope (SEM) images and physical images of the biodegradable plastics in the embodiments and comparative examples are as follows: Figure 4 (a is an embodiment, b is a comparative example; the small pictures in the upper right corners of a and b are the corresponding physical pictures).

[0058] Depend on Figure 4 It can be seen that the cross-section of the biodegradable plastic in the embodiment shows an obvious long-range arranged layered structure, which is formed by compressing and densifying the aerogel, namely the so-called "brick", while the cross-section of the biodegradable plastic in the comparative example is randomly arranged and presents a porous structure, which further confirms the significant difference in microstructure between the biodegradable plastic in the embodiment and the biodegradable plastic in the comparative example.

[0059] 4) Uniaxial tensile test (tested at room temperature): The biodegradable plastic in the embodiment (denoted as BFA) and the biodegradable plastic in the comparative example (denoted as FI) were cut into standard dumbbell-shaped samples (length 6 mm, width 2 mm, thickness 1.5 mm), and then the samples were fixed in the upper and lower clamps of an Instron 5965 electronic universal tensile testing machine (USA), the clamp spacing was adjusted to 8 mm, and a 100N sensor was used to perform a uniaxial tensile test at a rate of 10 mm / min. The test was completed when the sample broke, and then a stress-strain relationship curve was generated according to the data recorded by the tensile testing machine, and the corresponding Young's modulus and tensile work test result graphs were obtained. The test results are shown in FIG. Figure 5 (a is the stress-strain relationship curve, b is the Young's modulus and tensile work test results; ∥ indicates that the force is parallel to the sample layer, and ⊥ indicates that the force is perpendicular to the sample layer).

[0060] Depend on Figure 5 It can be seen that the Young's modulus and tensile work of the biodegradable plastic (BFA∥) in the embodiment are 560MPa and 0.7MJ / m 3 , which are 1.45 times and 5.2 times of the biodegradable plastic (FI) in the control example, indicating that the "brick-mud" structure formed in the biodegradable plastic in the example significantly increases the Young's modulus and tensile work of the material, giving the material high toughness.

[0061] 5) Three-point bending fracture test (tested at room temperature): The three-point bending fixture was installed on an Instron 5965 electronic universal tensile testing machine, and a 100N force sensor was used to record the load. The biodegradable plastic in the embodiment (referred to as BFA) and the biodegradable plastic in the comparative example (referred to as FI) were cut into rectangular samples (length 15 mm, width 3 mm, thickness 1.5 mm), and a 1.5 mm long U-shaped notch was polished on the sample. The sample was then placed on two supporting rollers of the bending device, and the span was adjusted to 12 mm to ensure that the sample was aligned with the loading device. During the test, the loading head was adjusted to contact the sample but no load was applied. The load was then applied to the set displacement at a constant rate of 0.04 mm / min, and then returned to the starting point at the same rate. The cyclic test (without interval time) was performed until the crack propagated and a force-displacement relationship curve was generated. The elastic contribution (J) was calculated according to the crack propagation length. el ), plastic contribution (J pl ) and toughness (J) comparison curve, the test results are as follows Figure 6 (a is a schematic diagram of the three-point bending fracture test, b is the force-displacement curve of the BFA∥ sample, c is the force-displacement curve of the BFA⊥ sample, and d is the force-displacement curve of the FI sample; ∥ indicates that the force is perpendicular to the sample layer, and ⊥ indicates that the force is parallel to the sample layer) and Figure 7 (a is the elastic contribution curve, b is the plastic contribution curve, and c is the toughness curve).

[0062] Toughness includes elastic part and plastic part, and its calculation formula is as follows:

[0063] J=J el +J pl

[0064]

[0065] E′=E / (1-v 2 )

[0066]

[0067]

[0068] In the formula, J el and J p1 Respectively represent the elastic contribution and plastic contribution of the specimen, E, v and K I They represent the elastic modulus, Poisson's ratio and stress intensity factor of the specimen respectively, P is the load applied to the specimen, S is the span, B is the thickness of the specimen, W is the total width of the specimen 3 mm, a is the crack length, f(a / W) is a geometric shape factor, which is a dimensionless function of a / W (ratio of crack length to specimen width), Ap1 is the plastic work, and b is the length of the residual unextended crack.

[0069] Depend on Figure 6 and Figure 7 It can be seen that the maximum toughness of the biodegradable plastic in the embodiment can reach 3.78 kJ / m 2 , which is about 3 times that of the biodegradable plastic in the comparative example (1.27 kJ / m 2 ), indicating that the "brick-mud" structure formed in the biodegradable plastic in the embodiment can induce plastic loss through the deflection of the crack tip during crack propagation, giving the material excellent fracture toughness.

[0070] 6) Recyclable processing: The biodegradable plastic in the embodiment is added to deionized water, shaken at room temperature for 3 hours, and then the obtained solution (uniform and transparent) is placed under a pressure of 5 Pa and a temperature of -80°C for freeze drying for 48 hours to obtain DNA powder, and then the DNA powder is used as a raw material to prepare DNA biodegradable plastic, thereby completing a closed-loop recycling process (recycling schematic diagram as shown in Figure 8 shown).

[0071] 7) Degradability test: 0.5 g of the biodegradable plastic in the embodiment was added to 2 mL of an aqueous solution containing DNase I (concentration of 5 U / μL), and a biodegradation experiment was performed at room temperature and the morphological changes were recorded. Optical photos were taken at the same time, and the electrophoretic bands of the degradation solution were detected by agarose gel electrophoresis. The optical photos of the morphological changes of the biodegradable plastic at different time points during the degradation process and the gel electrophoresis bands after complete biodegradation were obtained as shown in FIG. Fig. 9 (a is an optical photograph of morphological changes, b is a gel electrophoresis band diagram, and M1 and M2 in b represent standard DNA gel electrophoresis bands with molecular weights of 23kp and 5kp, respectively).

[0072] Depend on Fig. 9 It can be seen that by comparing the number of base pairs with the standard sample, it was found that the DNA band was blurred and the intensity was weakened, indicating that the biodegradable plastic can be completely biodegraded within 8 hours.

[0073] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing biodegradable plastics, characterized in that: The following steps are involved: 1) Dissolve onion DNA in water to prepare a DNA solution; 2) injecting the DNA solution into the mold for two-way freezing casting to obtain a DNA freezing block; 3) freeze-drying the DNA frozen block to obtain a DNA aerogel block; 4) placing the DNA aerogel block in a water vapor environment for annealing to obtain an annealed DNA aerogel block; 5) stacking a plurality of annealed DNA aerogel blocks and then compressing and densifying them to obtain biodegradable plastic.

2. The method for preparing biodegradable plastic according to claim 1, characterized in that: Step 1) The onion DNA is prepared by a preparation method comprising the following steps: rapidly freezing onions and then crushing them to prepare onion powder, adding the onion powder to a mixed solution of CTAB extraction buffer and 2-mercaptoethanol for incubation, adding chloroform and isoamyl alcohol and centrifuging, taking the clear liquid for alcohol precipitation, centrifuging, and taking the solid matter for washing and drying to obtain the onion DNA.

3. The method for preparing biodegradable plastic according to claim 2, characterized in that: The incubation is carried out at a temperature of 60° C. to 70° C., and the incubation time is 40 min to 60 min.

4. The method for preparing biodegradable plastic according to claim 2, characterized in that: The washing comprises the following steps: First wash with anhydrous ethanol, then wash with an ethanol solution with a mass fraction of 70% to 80%, and finally wash with water for multiple times.

5. The method for preparing the biodegradable plastic according to any one of claims 1 to 4, characterized in that: Step 2) The bidirectional freezing casting is carried out at a temperature of -80°C to -60°C, and the casting time is 30min to 60min.

6. The method for preparing the biodegradable plastic according to any one of claims 1 to 4, characterized in that: Step 3) The freeze drying is carried out under the conditions of a pressure of 3Pa to 7Pa and a temperature of -70°C to -50°C, and the freeze drying time is 48h to 72h.

7. The method for preparing the biodegradable plastic according to any one of claims 1 to 4, characterized in that: Step 4) The annealing is carried out in a water vapor environment with a relative humidity of 60% to 80%, and the annealing time is 15 minutes to 25 minutes.

8. The method for preparing the biodegradable plastic according to any one of claims 1 to 4, characterized in that: Step 5) The compression densification is carried out at a pressure of 10 MPa to 15 MPa, and the pressure holding time is 30 min to 40 min.

9. A biodegradable plastic, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the biodegradable plastic according to claim 9 in the fields of packaging, medical devices, 3D printing, agricultural tools or environmentally friendly consumer products.

Citation Information

Patent Citations

  • High-flexibility waste-wool-base biological plastic and preparation method thereof

    CN106750521A

  • DNA based biodegradable resin composition

    US20230167315A1

  • Composite bioplastic material

    WO2024115238A1